Volumetric analysis of liver fibrosis. - Leong, Yong Shin. (2013)
Liver fibrosis is accumulation of extracellular matrix in the liver tissue. It occurs in response to acute or chronic liver injury. There are a large range of causes for liver fibrosis, which include viral infection, autoimmune, drug-induced, cholestatic and metabolic diseases. Liver fibrosis ultimately leads to cirrhosis, the end-stage consequence of fibrosis within hepatic parenchyma. Cirrhosis is often characterized by presence of hepatic nodule, a hexagonal formation of extracellular matrix that encircles and isolates a portion of hepatic parenchyma. Hepatic nodule hinders blood flow within liver which detriment the normal functionality of the organ. Failure of the whole liver can occur if fibrosis becomes too extensive and by then there is no viable treatment available, except for liver transplant [1].